Analysis of the Use of Learning Media Through the Peer Tutor Toward Creative Thinking Skills and Interpersonal Communication of Preservice Teachers in Primary Teacher Education Programs - Siti Fatimah (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2019)
This study aims to analyze the use of instructional media through peer tutor on creative thinking skills and interpersonal communication of preservice teachers in primary teacher education Programs on earth material. This research is a quantitative study with a student research population for 2018/2019 academic year. The sampling technique is done by using saturated sampling technique that is the entire population is used as a research sample. The instruments used were observation sheets, questionnaire sheets, test sheets, and interview sheets. Data analysis techniques using the Mann Withney-U test. The analysis showed that: 1) there was an influence of learning media through peer tutor on creative thinking skills and interpersonal communication on earth material; 2) creative thinking skills and interpersonal abilities in the experimental class are better than the control class; 3) The aspect of fluency in creative thinking skills shows the highest score while the originality aspect shows the lowest score.